Trans Influence of Boryl Ligands in CO2 Hydrogenation on Ruthenium Complexes: Theoretical Prediction of Highly Active Catalysts for CO2 Reduction - Tian Liu (MDPI AG, 2021)
In this work, we study the trans influence of boryl ligands and other commonly used non-boryl ligands in order to search for a more active catalyst than the ruthenium dihydride complex Ru(PNP)(CO)H2 for the hydrogenation of CO2. The theoretical calculation results show that only the B ligands exhibit a stronger trans influence than the hydride ligand and are along increasing order of trans influence as follows: –H < –BBr2 < –BCl2 ≈ –B(OCH)2 < –Bcat < –B(OCH2)2 ≈ –B(OH)2 < –Bpin < –B(NHCH2)2 < –B(OCH3)2 < –B(CH3)2 < –BH2. The computed activation free energy for the direct hydride addition to CO2 and the NBO analysis of the property of the Ru–H bond indicate that the activity of the hydride can be enhanced by the strong trans influence of the B ligands through the change in the Ru–H bond property. The function of the strong trans influence of B ligands is to decrease the d orbital component of Ru in the Ru–H bond. The design of a more active catalyst than the Ru(PNP)(CO)H2 complex is possible.